The haematocrit and platelet target in polycythemia vera - Marcello Di Nisio; Tiziano Barbui; Leonardo Di Gennaro; Giovanna Borrelli; Guido Finazzi; Raffaele Landolfi; Giuseppe Leone; RosaMaria Marfisi; Ettore Porreca; Marco Ruggeri; Anne WS Rutjes; Gianni Tognoni; et al. (2006)
Summary Polycythemia vera (PV) is a chronic myeloproliferative disorder whose major morbidity and mortality are thrombohaemorragic events and progression to acute leukaemia or myelofibrosis. Whether the haematocrit and platelet count predict such complications remains unclear. The European Collaboration on Low‐dose Aspirin in Polycythemia Vera prospective study included 1638 PV patients. A total of 164 deaths (10%), 145 (8·85%) major thrombosis and 226 (13·8%) total thrombosis were encountered during 4393 person‐years follow‐up (median 2·8 years). In time‐dependent multivariable analysis, a haematocrit in the evaluable range of 40–55% was neither associated with the occurrence of thrombotic events, mortality nor with haematological progression in the studied population. The haematocrit of patients in the highest and lowest deciles at baseline was maintained within a narrow interval of haematocrit values ranging from 40% to 47% throughout follow‐up. High platelet count was associated with a lower progression rate to acute leukaemia/myelofibrosis, whereas it had no significant relationship with thrombotic events or mortality. Our findings do not suggest that the range of haematocrit (<55%) and platelet counts (<600 × 10 9 /l) we encountered in our population had an impact on the outcome of PV patients treated by current therapeutic strategies.